2018
DOI: 10.3389/fimmu.2018.00965
|View full text |Cite
|
Sign up to set email alerts
|

Tespa1 Deficiency Dampens Thymus-Dependent B-Cell Activation and Attenuates Collagen-Induced Arthritis in Mice

Abstract: Thymocyte-expressed, positive selection-associated 1 (Tespa1) plays an important role in both T cell receptor (TCR)-driven thymocyte development and in the FcεRI-mediated activation of mast cells. Herein, we show that lack of Tespa1 does not impair B cell development but dampens the in vitro activation and proliferation of B cells induced by T cell-dependent (TD) antigens, significantly reduces serum antibody concentrations in vivo, and impairs germinal center formation in both aged and TD antigen-immunized mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…cpt1aa is involved in fatty acid oxidation, lipeb breaks down triglycerides and pld1 feeds into the mTOR pathway to regulate fat levels [24][25][26] . Further, c3b is involved in apoptosis and phagocytosis, gpr1 influences glucose levels and tespa1 is required for B-cell activation [27][28][29] . These results reflect the biology of these fishes in vivo, as it has been shown that surface fish undergo higher lipid breakdown while cavefish synthesize more lipid and surface fish have an increased innate immune response compared to cavefish 5,7,21 .…”
Section: Sfl and Cfl Express Liver-specific Enzymesmentioning
confidence: 99%
“…cpt1aa is involved in fatty acid oxidation, lipeb breaks down triglycerides and pld1 feeds into the mTOR pathway to regulate fat levels [24][25][26] . Further, c3b is involved in apoptosis and phagocytosis, gpr1 influences glucose levels and tespa1 is required for B-cell activation [27][28][29] . These results reflect the biology of these fishes in vivo, as it has been shown that surface fish undergo higher lipid breakdown while cavefish synthesize more lipid and surface fish have an increased innate immune response compared to cavefish 5,7,21 .…”
Section: Sfl and Cfl Express Liver-specific Enzymesmentioning
confidence: 99%
“…However, the pathogenesis of RA remains incompletely understood, and researching the key genes underlying RA development remains a priority. Our previous studies found that Thymocyte-expressed positive selection-associated 1 ( Tespa1 ) plays a critical role in the pathogenesis of human rheumatoid arthritis and mice collagen-induced arthritis, thus defining Tespa1 as a key gene in the pathogenesis of RA ( 24 , 25 ). With the development of high-throughput sequencing and bioinformatic analytical techniques, DNA microarray has become an important method to obtain gene expression data of multiple diseases on a large scale and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mode of action in human B cells by Epratuzumab was observed to be elicited a downregulation of Syk/PLC2 signalling, including calcium flux, following BCR stimulation [116]. Thymocyte-expressed, positive selection-associated 1 (Tespa-1) is critical in thymic T cell development and activiation of mast cells via FcRI, as well as being of importance to B cell functions including proliferation, activation, germinal centre formation and serum antibody production [117]. Pathogenic B cells which form in the Tespa-1 KO mice in a collagen-induced arthritis model were impaired in PLC2 function, and associated calcium flux, thereby reducing the severity of their disease in comparison to control mice [117].…”
Section: J O U R N a L P R E -P R O O F Plc2 And Autoimmune Diseasementioning
confidence: 99%